Past, present and future of archival material as (non)persistent chemicalmaterial - with special focus on the problem of acetate decay or vinegar syndrome - Lavrenčič, Aleksander (Atlanti +, 2024)
Purpose: The purpose of this article is to show how important it is for archives to realize that the safe storage of originals is important for the preservation of material.Methodology: With the help of the story of the Indian Ishi from the beginning of the 20th century and the destruction of important film material, it was explained what are the consequences for the existence of cultural heritage because of irre-sponsible handling of film material.Results: The story of the collapse of film material that was stored in unsuita-ble conditions teaches us that we must pay attention to appropriate professional education. The damage caused by ignorance or carelessness in the handling of archival material is in most cases irreparable.Conclusions/findings: The decay of film material is not only a problem of audio-visual archives. Similar problems have been detected in all archives. Digitiza-tion enables easier access to the material and more secure storage, but there is still a need for professional, flawless storage of the original analog material in archival depots. This is the only way cultural heritage can be preserved for future generations.
Keywords: acetate decay; archives; arhivi; au-dio-visual archives; avdiovizualni arhivi; chemical deterioration; digitalizacija; digitisation; kemično propadanje; propadanje acetata